Boron‐Oxygen Bond Cleavage of Pinacolborane and Catecholborane Mediated by a Scandium Phosphinidene Complex. Issue 8 (5th June 2014) - Wang, Wei; Lv, Yingdong; Gou, Xiaofeng; Leng, Xuebing; Chen, Yaofeng
Abstract Reactions of bis‐scandium bridged phosphinidene complex, [LSc(μ‐PAr)]2 (L=MeC(NDIPP)CHC(Me)(N‐CH2CH2N(iPr)2), DIPP=2, 6‐(iPr)2C6H3; Ar=2, 6‐Me2C6H3) (1), with pinacolborane, catecholborane, and 9‐borabicyclo[3.3.1]nonane (9‐BBN) are reported. Complex 1 reacts with pinacolborane and catecholborane to give scandium pinacolate (2) and catecholate (3), showing BO bond cleavage. These two scandium complexes contain an unusual [P(Ar)B(H)P(Ar)]2− dianion, which displays a μ‐η2:η2 coordination model. On the other hand, reaction of complex 1 with 9‐BBN affords the BH bond cleavage product, 1, 3‐diphospha‐2, 4‐diboracyclobutane (4).